Aortic stiffness and distensibility in elite athletes: impact of discipline and gender. (25th November 2020) - Abuli, M; Sanz-De La Garza, M; Vidal, B; Doltra, A; Sarquella Brugada, G; Carvalho, S; Santiago, J; Rodas, G; Guasch, E; Sitges, M
Abstract: Background: Aortic remodeling in athletes is variable among sports disciplines with more ascending aorta (Asc Ao) dilatation in endurance (EAs) as compared to power athletes (PAs). Nevertheless, the impact of this differential remodeling on the Asc Ao functional properties is not well established. The aim of this study was to assess the distensibility and stiffness of the ascending aorta in endurance and power elite athletes in order to evaluate if this aortic remodeling implies functional changes. Methods: 119 elite athletes (61 EA and 58 PA, 49% female sex, mean age: 18.7±7.1 years) underwent standardized pre-participation screening with 12 lead ECG, transthoracic echocardiography and maximum stress test. Asc Ao diameter was measured from parasternal long axis views in 2D echocardiography. The aortic distensibility index (ADi) was calculated as 2 × (systolic Asc Ao diameter − diastolic Asc Ao diameter) / (diastolic Asc Ao diameter) × (pulse pressure) (cm –2 dyn –1 10 –6 ). Aortic stiffness (AS) index was defined as Ln (systolic blood pressure/diastolic blood pressure) / (systolic Asc Ao diameter − diastolic Asc Ao diameter)/diastolic proximal Asc Ao diameter. Results: Globally, EA presented larger AscAO, both in absolute and indexed values, than PA (28±3.0 vs 26±3.0cm, p<0.001 and 16.4±1.5 vs 15.7±1.9cm, p<0.05, while were no differences in AS or ADi) (Figure 1A). Nevertheless, ADi in male EAs was higher than in male PAs (ADi: 4.3±1.7 vs 3.2±1.3 cm 2 /dyn/10 –6, p<0.05) and AS was lower (AS: 4.7±1.7 vs 6.3±3.8, P<0.005) (Figure 1B and 1C). Female athletes presented higher ADi (ADi: 4.7±1.9 vs 4.0±1.6 cm, p<0.05) and a trend towards lower AS (4.8±2.9 vs 5.1±2.6, p: 0.4) than male athletes. There were no differences in AS or ADi between female EAs and PAs. Conclusion: Male EAs showed an increased aortic distensibility with lower stiffness as compared to that observed in male PAs. This difference was not observed in female EAs and PAs, potentially due to better baseline distensibility with less room for improvement with endurance training. Funding Acknowledgement: Type of funding source: None